The clinical utility of new cardiac imaging modalities in Australasian clinical practice. Issue 3 (1st August 2016) - Hamilton‐Craig, Christian; Chan, Jonathan
Summary: Cardiac imaging is a rapidly evolving field, with improvements in the diagnostic capabilities of non‐invasive cardiac assessment. We review the two main emerging technologies in cardiac imaging: computed tomography coronary angiography (CTCA) to evaluate chest symptoms and to exclude coronary artery disease; and cardiovascular magnetic resonance (CMR) for evaluating cardiac morphology, function and presence of scar. CTCA is an excellent "rule out" test, with a negative predictive value approaching 100%. Radiation exposure is no longer a concern for CTCA, with doses routinely < 5 mSv, and as low as < 1 mSv in selected patients. CTCA is useful for excluding coronary artery disease, investigating the anatomy of coronary anomalies or fistulae, and for the patency of coronary bypass grafts. CMR is the reference test for the accurate quantitation of left ventricular and right ventricular size and function. CMR has no ionising radiation, making it particularly suitable for patients with heart failure or congenital heart disease who require longitudinal follow‐up. Evaluation of cardiomyopathies (hypertrophic, ischaemic, infiltrative, myocarditis, iron overload or idiopathic) is a unique strength of CMR. Stress perfusion CMR has a strong evidence base and improved spatial and temporal resolution compared with nuclear single‐photon emission computed tomography.